Crime on the Court - McCormick, Robert E.; Tollison, Robert D. (Journal of Political Economy, 1984)
This paper addresses the question, What happens to the arrest rate when the number of law enforcers increases? One implication of the analysis is that arrest statistics are a poor instrumental variable for judging the quality of law enforcement. Increasing the number of police can increase of decrease the number of arrests. An increased probability of arrest induces fewer criminal acts; hence the ambiguity. Because of this result, we apply the theory in the setting of college basketball. We find a large reduction, 34 percent, in the number of fouls committed during a basketball game when the number of referees increases from two to three. Additional empirical evidence is presented which suggests that this elastic supply of basketball crime is due to more competent officiating and cleaner play.